Cytokines and Colony Stimulating Factors Methods and Protocols - Körholz, Dieter; Kiess, Wieland; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
Enormous effort has been spent developing many new laboratory techniques for studying immune cells and the immune system, not only to increase fundamental understanding, but also to procure therapeutic success in a clinical setting. In Cytokines and Colony Stimulating Factors: Methods and Protocols, leading laboratory experts describe for the novice investigator a host of novel technologies and molecular techniques specifically designed to study cellular immunology and promote its gene therapy applications. Presented in step-by-step detail to ensure ready reproducibility, these protocols range from flow cytometric techniques to detect cytokines and growth factors in different specimens, to methods for generating and expanding dendritic cells and hematopoietic progenitors from different origins. Each proven method has been fine-tuned for experimental successs by the investigator who developed it, and includes notes on troubleshooting and avoiding potential pitfalls. Although the protocols require little previous experience, even highly skilled researchers will augment their experimental range with many novel timesaving techniques. Cutting-edge and highly practical, Cytokines and Colony Stimulating Factors: Methods and Protocols provides researchers a carefully evaluated set of powerful tools for successful experimental research on cytokines and their role in gene therapy.
Primary Immunodeficiencies Caused by Defects of Cytokines and Cytokine Receptors -- Detection Assays for Cytokines and Growth Factors -- Intracellular Detection of T-Cell Cytokines -- Analysis of Cytokine Profiles in Human Skin -- Intracytoplasmic Detection of Proinflammatory Cytokines and Chemokines in Monocytes by Flow Cytometry -- Flow-Cytometric Immune Function Methodology for Human Peripheral Blood Dendritic Cells -- Evaluation of the Frequency of Virus-Specific CD8+T Cells by Cytokine Flow Cytometry -- Detection of Common Cytokine and Colony Stimulating Factor Gene Polymorphisms -- Apoptosis Induction by TRAIL -- Angiogenic Cytokines -- Detection Assays for Cytokines and Growth Factors -- Experimental Strategies for Combined Suicide and Immune Cancer Gene Therapy -- Gene Therapy with Plasmids Encoding Cytokine- or Cytokine Receptor-IgG Chimeric Proteins -- Interferon-? Gene Therapy for the Treatment of Arthritis -- Gene Gun-Based In Vivo Gene Transfer -- Purification of the Eucaryotic Heat-Shock Proteins Hsp70 and gp96 -- Genetic Engineering of a Recombinant Fusion Protein Possessing an Antitumor Antibody Fragment and a TNF-? Moiety -- Genetic Engineering of Dendritic Cells by Adenovirus-Mediated TNF-? Gene Transfer -- Retroviral Transfer of T-Cell Receptor Genes into Human Peripheral Blood Lymphocytes -- Gene Transfer to Articular Chondrocytes with Recombinant Adenovirus -- Gene Therapy of X-Linked Severe Combined Immunodeficiency -- Gene Transfer for Generation of Tumor and Leukemia Vaccines -- Cytokine Gene Delivery into the Central Nervous System Using Intrathecally Injected Nonreplicative Viral Vectors -- Ex Vivo Cell Expansion -- In Vitro Regulation of Colony Stimulating Factor-Mediated Hematopoiesis in Healthy Individuals and Patients with Different Types of Myeloproliferative Disease -- In Vitro Generation of Dendritic Cells from Cord Blood CD34+Hematopoietic Progenitors Cells -- Generation of TransgenicT Cells from Human CD34+Cord Blood Cells -- Ex Vivo Expansion of Umbilical Cord Blood Cells on Feeder Layers -- Ex Vivo Production of Cord Blood CD34+Derived Myeloid Precursors After Serum-Free Static Culture -- 27 Ex Vivo Expansion of Hematopoietic Stem Cells -- 28 Large-Scale Ex Vivo Expansion of Human Megakaryocytes for Clinical Use -- Cytokine-Mediated Expansion of Human NOD-SCID-Repopulating Cells -- Maturation and Differentiation of Dendritic Cells -- Differentiation of Human Antigen-Presenting Dendritic Cells from CD34+Hematopoietic Stem Cells In Vitro -- Dendritic Cell Development from Mobilized Peripheral Blood CD34+Cells -- In Vitro Maturation of Dendritic Cells from Blood Progenitors -- Generation of Human Type 1- and Type 2-Polarized Dendritic Cells from Peripheral Blood -- Preparation of Human Dendritic Cells for Tumor Vaccination -- Generation of Leukemic Dendritic Cells from Patients with Acute Myeloid Leukemia.
Keywords: Immunology; Immunology